Dietary Lactiplantibacillus plantarum KX041 attenuates colitis-associated tumorigenesis and modulates gut microbiota - Tao Wang; Panpan Wang; Li Yin; Xiuchao Wang; Yuanyuan Shan; Yanglei Yi; Yuan Zhou; Bianfang Liu; Xin Wang; Xin Lü (Food Science and Human Wellness)
Colorectal cancer (CRC) is one of the most common cancers and supplementation of probiotics may be a promising intervention method. The present study aimed to investigate the anti-CRC effects of Lactiplantibacillus plantarum KX041 on a CRC mouse model. The CRC mice were induced by 10 mg/kg azoxymethane and 2 % dextran sulfate sodium. L. plantarum KX041 was orally administrated once daily (1 × 109 CFU/mouse). Results showed that L. plantarum KX041 could significantly inhibit inflammation, tumor formation, and induce tumor cells apoptosis. Moreover, this probiotic could ameliorate the damage of intestinal barrier by recovering tight junction protein expression (like Occludin, Claudin-1, and ZO-1) and preventing goblet cell loss. Furthermore, the oxidative stress was alleviated by increasing the level of antioxidant mediators (like GSH and SOD) and reducing the level of oxidative mediators (like MDA and MPO). In addition, treatment with L. plantarum KX041 could directly regulate gut microbiota, thereby increasing the abundance of beneficial bacteria (like SCFAs-producing bacteria, Akkermansia) and decreasing the abundance of harmful bacteria (like pro-inflammatory bacteria, Parasutterella), which in turn raised SCFAs levels and lowered LPS levels. In conclusion, L. plantarum KX041 could effectively ameliorate CRC via reshaping intestinal microenvironment, alleviating inflammation, maintaining intestinal permeability, and attenuating oxidative stress.